1880 Rev. Code of the Stat. Laws of the State of Miss. 776-77, ch. 77, § 2985 - (:unkn) unknown (General Publisher, 1880)
Any person, not being threatened with, or having good and sufficient reason to apprehend an attack, or travelling (not being a tramp) or setting out on a journey, or a peace officer, or deputy in discharge of his duties, who carries concealed, in whole or in part, any bowie knife, pistol, brass or metallic knuckles, slung-shot, or other deadly weapon of like kind or description, shall be deemed guilty of a misdemeanor,
--
Keywords: CARRY - CONCEALED